Differentiation of citrus tristeza virus isolates by serological analysis of p25 coat protein peptide maps - Albiach-Martí, María R.; Guerri, José; Cambra, Mariano; Garnsey, Stephen M.; Moreno, Pedro (2017)
A procedure was developed to purify rapidly and easily a sufficient quantity of native p25 coat protein (CP) to allow comparison of five isolates of citrus tristeza virus (CTV) by serological analysis of peptide maps, using monoclonal and polyclonal antibodies. CTV particles were concentrated by centrifugation and purified by agarose gel electrophoresis. The CP was extracted from gel slices riched in virions and protein yields were about three times greater than those obtained previously and of comparable purity. The purified CP was partially digested with either V8 or papain endo-protease, and the peptides generated were separated and electroblotted to a membrane. Protein blots were tested with four monoclonal antibodies and one source of polyclonal antibodies. The serological maps generated by papain allowed differentiation of all the isolates examined, and those generated by V8 endoprotease allowed discrimination of four of the five isolates tested. Some of these isolates had been indistinguishable based on their reactivity in DASI-ELISA, dsRNA pattern and biological characterization. Serological analysis of peptide maps, as described below, allowed accurate comparison of CTV isolates with minimum amounts of p25 CP and proved superior to other techniques for discriminating CTV isolates. (C) 2000 Published by Elsevier Science B.V. All rights reserved.